Space plasma physics: a review - Tsurutani, Bruce T.; Zank, Gary P.; Sterken, Veerle J.; Shibata, Kazunari; Nagai, Tsugunobu; Mannucci, Anthony J.; Malaspina, David M.; Lakhina, Gurbax S.; Kanekal, Shrikanth G.; Hosokawa, Keisuke; Horne, Richard B.; Hajra, Rajkumar; et al. (My University, 2022)
Owing to the ever-present solar wind, our vast solar system is full of plasmas. The turbulent solar wind, together with sporadic solar eruptions, introduces various space plasma processes and phenomena in the solar atmosphere all the way to Earth’s ionosphere and atmosphere and outward to interact with the interstellar media to form the heliopause and termination shock. Remarkable progress has been made in space plasma physics in the last 65 years, mainly due to sophisticated in situ measurements of plasmas, plasma waves, neutral particles, energetic particles, and dust via space-borne satellite instrumentation. Additionally, high-technology groundbased instrumentation has led to new and greater knowledge of solar and auroral features. As a result, a new branch of space physics, i.e., space weather, has emerged since many of the space physics processes have a direct or indirect influence on humankind. After briefly reviewing the major space physics discoveries before rockets and satellites (Section I), we aim to review all our updated understanding on coronal holes, solar flares, and coronal mass ejections, which are central to space weather events at Earth (Section II), solar wind (Section III), storms and substorms (Section IV), magnetotail and substorms, emphasizing the role of the magnetotail in substorm dynamics (Section V), radiation belts/energetic magnetospheric particles (Section VI), structures and space weather dynamics in the ionosphere (Section VII), plasma waves, instabilities, and waveparticle interactions (Section VIII), long-period geomagnetic pulsations (Section IX), auroras (Section X), geomagnetically induced currents (GICs, Section XI), planetary magnetospheres and solar/stellar wind interactions with comets, moons and asteroids (Section XII), interplanetary discontinuities, shocks and waves (Section XIII), interplanetary dust (Section XIV), space dusty plasmas (Section XV), and solar energetic particles and shocks, including the heliospheric termination shock (Section XVI). This article is aimed to provide a panoramic view of space physics and space weather.
Keywords: Geomagnetic storms; Ionosphere; Magnetosphere; solar radiation; solar system; space missions